Interleukin 17A as a good predictor of the severity of Mycoplasma pneumoniae pneumonia in children. Issue 1 (December 2017) - Yang, Mingyue; Meng, Fanzheng; Wang, Kuo; Gao, Man; Lu, Ruihua; Li, Mengyao; Zhao, Fangxing; Huang, Lijuan; Zhang, Yining; Cheng, Genhong; Wang, Xiaosong
Abstract Early distinction between severeMycoplasma pneumoniae pneumonia (MPP) and mild MPP is still difficult. The aim of this study was to analyze cytokines in bronchoalveolar lavage fluid (BALF) and explore predicting factors of severe MPP in children. Retrospective analysis was performed on 150 children with MPP or bronchial foreign body (FB) admitted in our hospital. The mRNA levels of IL17A were found significantly lower in severe MPP group comparing with mild MPP group or FB group. However, no significant difference was found in the levels of IL4, IL10 or interferon beta1 (IFNβ1) between the two groups. Receiver operator characteristic (ROC) curve analysis showed that IL17A can be used to distinguish severe MPP from mild MPP. These results were confirmed in a validation cohort including 40 MPP children from another hospital. IL17A levels were correlated with some clinical characters, such as refractoriness and pleural effusion. Lower IL17A levels were more likely to be found in refractory MPP children or in MPP children with pleural effusion. Moreover, the protein levels of IL17A in BALF were also found greatly decreased in children with severe MPP. Thus, decreased IL17A levels in BALF may be a valuable biomarker to identify severe MPP in children.